(untitled) (Journal of Psychiatrists’ Association of Nepal, 2014)
HIV/AIDS epidemic remains among the most significant challenges to public healthcare systems worldwide . There are approximately 50,200 people living with HIV/AIDS (PLHA) in Nepal among the total 33 million PLHAs . Human Immunodeficiency Virus (HIV) infection/Acquired Immunodeficiency Syndrome (AIDS) is a significant cause of death and disability, especially in developing countries. Studies have shown that there is a bidirectional link between Mental illness and HIV/AIDS. However, mental illnesses are under detected in HIV/AIDS care settings. In spite of a good financial support from international partners, PLHA in Nepal do not receive necessary psychiatric services. Psychiatric illness in patients with HIV/AIDS has been associated with negative health behaviors and poorer clinical outcomes. This article, therefore, aims to highlight this issue among the stakeholders by reviewing the research on the topic in Nepal and making them aware of the need to DOI: http://dx.doi.org/10.3126/jpan.v2i2.9718 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 6-10